Correlation of uterine artery mean velocity with gestational age as indicator of uterine vascular perfusion - Apaza Valencia, John (2015)
Objectives: To determine correlation of the uterine artery mean velocity with gestational age as indicator of uterine vascular perfusion. Design: Cross-sectional study. Setting: Hospital III Honorio Delgado, Arequipa, Peru. Participants: Pregnant women. Interventions: To pregnant women between 14-41 weeks of gestation admitted to the hospital for routine ultrasound evaluation without evidence of pathology both uterine arteries average mean velocity (MnV) was calculated and correlated with gestational age. Correlation of average MnV in the second (14-28 weeks) and third (29-41 weeks) trimesters and MnV 5th percentile were determined. Main outcome measures: Both uterine arteries mean velocity (MnV) and correlation with gestational age. Results: Average age of the 138 pregnant women was 26.4 years and MnV correlation coefficient to gestational age was r = 0.556 (r2 = 0.31). Correlation coefficients were r = 0.634 (r2 = 0.40) and r = 0.32 (r2 = 0.001) respectively in the second and third trimesters. MnV 5th percentile average in the third trimester (29-41 weeks) was 67.50 cm/s. Conclusions: There was MnV correlation with gestational age. Values below the 5th percentile for gestational age could be used as indicators of uterine vascular hypoperfusion in pregnant women in the second and third trimesters.